Local Government’s role in Aceh’s sharia banking transition: legal and institutional perspectives - Istianah Zainal Asyiqin; Yanis Rinaldi (Legality : Jurnal Ilmiah Hukum, 2025)
This study examines the Aceh Government’s authority in converting conventional financial institutions into Sharia-compliant entities under Aceh Qanun No. 11 of 2018 and evaluates its practical implementation. Employing a normative legal research approach, the study analyses statutory regulations, legal principles, and doctrinal interpretations while incorporating historical context and relevant precedents. The findings confirm that the Aceh Government is legally mandated to oversee this financial transformation. However, several critical challenges impede its execution, including inadequate infrastructure, limited Sharia-compliant financial products, restricted access to Sharia banking capital, minimal adoption by non-banking financial institutions, and low financial inclusion. Among these, the lack of financial infrastructure and product diversity emerge as the most significant obstacles. To enhance the effectiveness of this transition, strategic interventions are necessary. These include expanding Sharia banking infrastructure, introducing diversified and innovative financial products, facilitating broader capital access for Sharia-compliant financial institutions, and strengthening financial literacy programs. A multi-stakeholder approach, integrating government agencies, financial institutions, and the community, is essential to establishing a robust and sustainable Sharia financial system in Aceh.